Nikolay Volodos – endoprosthesis of aorta history - Yashchuk, N. S.; Cherpak, B. V.; Ditkivskyy, I. O.; Kravchenko, V. I. (Ukrainian Journal of Cardiovascular Surgery, 2016)
It is world known fact – first stent-graft was invented in 1985 in former Soviet Union in Kharkiv by Nikolay Volodos.